2020
DOI: 10.1007/jhep03(2020)103
|View full text |Cite
|
Sign up to set email alerts
|

Search for lepton flavour violating decays of a neutral heavy Higgs boson to μτ and eτ in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV

Abstract: Search for lepton flavour violating decays of a neutral heavy Higgs boson to µτ and eτ in proton-proton collisions at √ s = 13 TeV The CMS collaboration

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Thus, approximately a region with |A eµ | above 60 GeV is eliminated. The above only demonstrate the stringency of the constraints on the first two generations of the off-diagonal Yukawa couplings arising from the null observation of µ → eγ [130] along with the CMS results on the first two generations [132,162]. Figure 9b is not so different from figure 5b indicating only an insignifant influence.…”
Section: Results For Varying Bino and Slepton Massesmentioning
confidence: 68%
“…Thus, approximately a region with |A eµ | above 60 GeV is eliminated. The above only demonstrate the stringency of the constraints on the first two generations of the off-diagonal Yukawa couplings arising from the null observation of µ → eγ [130] along with the CMS results on the first two generations [132,162]. Figure 9b is not so different from figure 5b indicating only an insignifant influence.…”
Section: Results For Varying Bino and Slepton Massesmentioning
confidence: 68%
“…For validation, we have generated the backgrounds for √ s = 13 TeV using Madgraph@NLO[111] and compared with the background event expectation as given in the CMS paper[110]. We have found that the backgrounds are consistent with the CMS background numbers up to 97% .…”
mentioning
confidence: 88%
“…Therefore the final state of our interest is + − + / E T . The SM backgrounds that give rise to similar final states consist of τ τ/ee/μμ, t t, W ± +jets, di-boson, SM Higgs [35,110]. The major and irreducible background turns out to be the leptonic final state of τ τ .…”
Section: Collider Searchesmentioning
confidence: 99%
“…the recent search bounds by CMS [53] turns out to be more stringent on the product ρ tt ρ τµ than from the recent Belle measurement of τ → µγ [54]. This means that a hint could well appear with full Run 2 data, as CMS only used 36 fb −1 data at 13 TeV in Ref.…”
Section: Possible Implications Of Muon G-2 In G2hdmmentioning
confidence: 99%
“…This means that a hint could well appear with full Run 2 data, as CMS only used 36 fb −1 data at 13 TeV in Ref. [53].…”
Section: Possible Implications Of Muon G-2 In G2hdmmentioning
confidence: 99%